Stereoselective Synthesis of Polyketide Segments of Nemamide A and Euglenatides D–E - Sharma, Himangshu; Paul, Sujan; Goswami, Rajib Kumar (Synlett, 2024)
A convergent strategy for the stereoselective synthesis of polyketide segments of hybrid natural products nemamide A and euglenatides D–E has been developed for the first time. The salient features of this gram-scale synthesis include Trost–Rychnovsky alkyne rearrangement, HWE olefination, regioselective epoxide ring opening, Prins–Ritter cyclization, and subsequent reductive cleavage of the substituted THP ring. The optimized route is modular and could be tunable to access the other polyketide counterparts of these families of metabolites.
Keywords: natural products; nemamide A; euglenatides D–E; Trost–Rychnovsky alkyne rearrangement; Prins–Ritter cyclization